2001
DOI: 10.1046/j.0022-3042.2001.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that glucokinase regulatory protein is expressed 
and interacts with glucokinase in rat brain

Abstract: Our previous description of functional glucokinase isoforms in the rat brain has opened new questions concerning the presence of glucokinase regulatory protein in the brain and the functional role of its interactions with glucokinase. In this study, we found glucokinase regulatory protein mRNA in rat brain, pancreatic islets and liver. In addition, we found two other variant splicing isoforms, both identi®ed in hypothalamus, pancreatic islets and liver. In situ hybridization studies revealed the presence of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 46 publications
(89 reference statements)
2
65
0
1
Order By: Relevance
“…Finally, it is still unclear how GK, with its high K m , might mediate neuronal glucosensing at physiological brain glucose levels (4,10,11). Like the ␤-cell, which expresses a similar isoform of GK but not GKRP (27,32), glucosensing neuron GKRP expression was too infrequent for it to be a significant regulator of GK activity that might bring the functional K m of GK activity down to appropriate brain glucose levels (11,12,63). There are also several differences between GE neurons and pancreatic ␤-cells.…”
Section: Characterization Of Vmn Glucosensing Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is still unclear how GK, with its high K m , might mediate neuronal glucosensing at physiological brain glucose levels (4,10,11). Like the ␤-cell, which expresses a similar isoform of GK but not GKRP (27,32), glucosensing neuron GKRP expression was too infrequent for it to be a significant regulator of GK activity that might bring the functional K m of GK activity down to appropriate brain glucose levels (11,12,63). There are also several differences between GE neurons and pancreatic ␤-cells.…”
Section: Characterization Of Vmn Glucosensing Neuronsmentioning
confidence: 99%
“…However, it is unclear how GK, with a K m for glucose phosphorylation of 8 -10 mmol/l (28 -31), might regulate neuronal glucosensing when physiological brain glucose levels are in the 0.5-3.5 mmol/l range (11,12). One possibility is that the GK regulatory protein (GKRP), which inhibits GK activity in the liver and is present in the brain (32), might possibly lower the functional K m of GK.…”
mentioning
confidence: 99%
“…Production of recombinant wild-type and mutant glutathione S-transferase-glucokinase Recombinant human wild-type beta cell GCK fused to glutathione S-transferase (GST; to form GST-GCK) was prepared as described previously [9]. MODY-associated mutations were introduced into the GST-GCK construct by PCR using a kit (QuikChange II Site Directed Mutagenesis Kit; Stratagene, La Jolla, CA, USA).…”
Section: Subjectsmentioning
confidence: 99%
“…This specific function of GCK is based on the particular kinetic characteristics of this enzyme, which include a low affinity for glucose, cooperativity with this substrate, and a lack of end-product inhibition at physiological concentrations. In addition, GCK activity is regulated through protein-protein interactions by the glucokinase (hexokinase 4) regulator (GCKR, also known as glucokinase regulatory protein [GKRP]), which acts as a competitive inhibitor with respect to glucose and also regulates the nucleo-cytoplasmic localisation of the enzyme [7][8][9]. In addition, GCK has been shown to associate with other partners, such as the bifunctional enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB1, also known as PFK2) [10,11], a dual specificity phosphatase [12], the neuronal isoform of nitric oxide synthase [13], the proapoptotic Bcell leukaemia/lymphoma 2 (BCL2) family member BCL2-antagonist of cell death (BAD) [14] and the precursor of the propionyl-CoA carboxylase beta subunit [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that GK may recognize elevations in plasma glucose levels after food ingestion and its interactions with the glucokinase regulatory protein (GKRP) may facilitate the functioning of glucose-sensing sites located in selective neurons of the hypothalamus and hindbrain (Alvarez et al 1996(Alvarez et al , 2002. In keeping with this proposal, groups of these cells containing orexigenic and anorexigenic peptides and their receptors may produce integrated responses to modifications in metabolites, enabling them to act as sensors of glucose circulating levels.…”
Section: Introductionmentioning
confidence: 99%